RETRACTED: Organizational and Economic Mechanism of Customer Relationship Management under the Era of Digital Transformations - Kwilinski Aleksy; Trushkina Nataliia; Birca Iulita; Shkrygun Yuliya (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 456, 00002 (2023), https://doi.org/10.1051/e3sconf/202345600002